ANKYLOSING SPONDYLITIS - Soldatenko, I. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Etiologic, epidemiologic, pathogenic and clinical description of ankylosing spondylitis are discussed in the lectures. Basic approaches to diagnostics, medical treatment and prophylaxis of disease are represented.